2014
DOI: 10.1111/jasp.12255
|View full text |Cite
|
Sign up to set email alerts
|

Buyer beware of your shadow: how price moderates the effect of incidental similarity on buyer behavior

Abstract: Using both a lab experiment and actual transaction data, we investigated whether and how incidental similarities (e.g., shared letters between buyer and seller's name) might influence buyer behavior. Particularly, while prior work suggests that consumers generally prefer incidental similarity, we use the context of Internet auctions to show that this preference reverses when prices are high. Under these conditions, buyers avoid incidentally similar sellers. We speculate that this effect is tied to individuals'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…New Zealand has an open-door immigration policy and is subsequently a country with a great deal of diversity. As reported by Statistics NZ (2019), more than 100,000 short-term international visitors, and new permanent and long-term migrants from all over the world arrived in New Zealand in 2018. New Zealand businesses, especially banks, recognize that this significant influx has massive future potential for the business market.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…New Zealand has an open-door immigration policy and is subsequently a country with a great deal of diversity. As reported by Statistics NZ (2019), more than 100,000 short-term international visitors, and new permanent and long-term migrants from all over the world arrived in New Zealand in 2018. New Zealand businesses, especially banks, recognize that this significant influx has massive future potential for the business market.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Van Zalk and Denissen (2015) emphasize that customers interact more frequently with sellers when they receive more information about the sellers, thus minimizing their uncertainty about future behaviors and improving their relationship. In addition, consumers who are motivated to interact with sellers (Kwok and Xie 2018; Kachersky et al , 2014) and utilize their time well during interactions (Ankitha and Basri, 2019) will significantly contribute to building successful relationships. In spite of academic recognition of the critical role interaction plays in firm–customer satisfaction relationships, the effect of similarity, interaction intensity and customer satisfaction with a banker has been less researched.…”
Section: Introductionmentioning
confidence: 99%
“…A handful of empirical findings suggest a negative impact of incidental similarity cues. The presence of an incidental similarity cue can have an adverse effect on consumer responses when a similar service provider displays negative behaviors (Jiang et al, 2010) or when prices suggested by a similar seller are too high (Kachersky et al, 2014). We provide a more nuanced understanding of incidental similarity cues by demonstrating a boundary condition for the negativity effect.…”
Section: Theoretical Implicationsmentioning
confidence: 84%
“…Therefore, it is necessary to explore whether this kind of interpersonal similarity effect still works in the new short video context. Second, from the perspective of research, the research on similarity and its consequences stays in a positive perspective (Guéguen et al, 2011;Brack and Benkenstein, 2012;Kachersky et al, 2014), ignoring the possible negative effects, which limits the comprehensive understanding of similarity effects to a certain extent. Third, the study lacks consideration of differences in individual cognitive motivations.…”
Section: Introductionmentioning
confidence: 99%